ChemInform Abstract: Palladium Catalyzed Direct Allylation of Azlactones with Simple Allylic Alcohols in the Absence of Any Activators. Issue 5 (February 2015) - Zhou, Hui; Yang, Huameng; Yin, Hongyu; Liu, Muwen; Xia, Chungu; Jiang, Gaoxi
Abstract The first efficient example of the direct allylic alkylation of azlactones with simple allylic alcohols using only Pd(PPh3)4 as catalyst under neutral conditions by substrate self‐assisted activation strategy is reported.